Optimization Of The Role Of Village-Owned Enterprise (BUMDES) In Developing Tourism Communication Strategies Based On Social Media - Perdana, Inco Hary; Winarto, Intan Permata Dewi (Universitas 17 Agustus 1945 Surabaya, 2024)
This research explores the potential of Village-Owned Enterprises (BUMDes) in developing tourism communication strategies, with a case study on the Tumpeng Menoreh tourist destination in Kulon Progo Regency. It employs a post-positivist approach with qualitative methodology, involving semi-structured interviews, social media platform observations, and document analysis. Rhetorical communication strategies and SWOT analysis are used to evaluate the effectiveness of social media in promoting tourism. The findings indicate that BUMDes has leveraged Instagram to enhance the visibility and accessibility of Tumpeng Menoreh through engaging visual content and narratives based on local culture. This strategy has successfully attracted visitors and empowered the local community, although challenges related to accessibility and reliance on influencers remain. The study concludes by emphasizing the importance of more structured strategic planning and diversification of social media platforms to achieve sustainable tourism. Keywords: BUMDes, tourism communication, social media, Tumpeng Menoreh, Instagram